Clinical and Functional Characterization of Novel AGL Variants in Two Families with Glycogen Storage Disease Type III - Tingting Yu; Hao Fu; Aoyu Yang; Yan Liang (International Journal of Endocrinology)
Purpose. Glycogen storage disease type III (GSDIII) is a uncommon autosomal recessive inherited metabolic disorder, which is caused by variants in the AGL gene. The purpose of this study was to elucidate the clinical and functional features of two novel variants in two families with GSDIIIa. Methods. We collected the clinical and laboratory data of the two patients. Genetic testing was performed using GSDs gene panel sequencing, and the identified variants were classified according to the American College of Medical Genetics (ACMG) criteria. The pathogenicity of the novel variants was furthermore assessed through bioinformatics analysis and cellular functional validation experiments. Results. The two patients were hospitalized with abnormal liver function or hepatomegaly, which was characterized by remarkably elevated liver enzyme and muscle enzyme levels, as well as hepatomegaly, and were eventually diagnosed with GSDIIIa. Genetic analysis detected two novel variants of AGL gene in the two patients: c.1484A > G (p.Y495C), c.1981G > T (p.D661Y). Bioinformatics analysis indicated that the two novel missense mutations most likely altered the protein’s conformation and therefore made the enzyme it encodes less active. Based on the ACMG criteria, both variants were considered likely pathogenic, in accordance with the functional analysis results, which demonstrated that the mutated protein was still localized in the cytoplasm and that the glycogen content of cells transfected with the mutated AGL was increased compared to cells transfected with the wild-type one. Conclusion. These findings indicated that the two newly identified variants in the AGL gene (c.1484A > G; c.1981G > T) were undoubtedly pathogenic mutations, inducing a slight reduction in glycogen debranching enzyme activity and a mild increase in intracellular glycogen content. Two patients who visited us with abnormal liver function, or hepatomegaly, improved dramatically after treatment with oral uncooked cornstarch, but the effects on skeletal muscle and myocardium required further observation.